Advances in Spatial Data Handling Geospatial Dynamics, Geosimulation and Exploratory Visualization - Timpf, Sabine; Laube, Patrick (Advances in Geographic Information Science, 2013)
This volume is based on the reviewed and edited proceedings of the International Symposium on Spatial Data Handling 2012, held in Bonn. The 15th SDH brought together scholars and professionals from the international GIScience community to present the latest research achievements and to share experiences in Geospatial dynamics, geosimulation and exploratory visualization.